THE ROLE OF CULTURE IN WRITING DEVELOPMENT - Yozilova, Feruza Nurmamat qizi; Maksudova , Khilola Ferdinantovna (Innovative Development in Educational Activities, 2023)
In developing writing skills culture plays a crucial role. As a writer his works will definitely be impacted by the culture he is surrounded by and, later the writer is likely to impact the culture of the community with his works. In different geographical locations writing is taught in different ways. The presence of cultural influence is obvious, especially in L2 writing classroom. However, western rules of academic writing have become a “right way of writing” for a long time. Even though highly popular western process pedagogy in writing classes have been supported by many language teachers so far, some scientists question the benefits of this methodology applied in nonnative ESL/EFL classrooms. On the journey of teaching writing to nonnative learners the knowledge of Contrastive Rhetoric and skillful delivery of cultural awareness to learners plays a huge role in the successful learning process. To understand the differences in cultures, some scientists offer graphic representations of cultural thought patterns of various languages.